The Effect of a Combination of Autogenic and Benson Relaxation on Sleep Quality among Pregnant Women with Hypertension - Esa Rosyida Umam; Agus Sulistyono; Esti Yunitasari (International Journal of Nursing and Health Services (IJNHS), 2020)
Physical changes, such as changes in body habitus, and hormonal changes, including dramatic increases in estrogen and progesterone, are recognized contributors to sleep disturbance in pregnancy. The study aimed to examine the effect of combined Autogenic and Benson relaxation on sleep quality in pregnant women with hypertension. A quasi-experimental, pre-test, and post-test with a control group was applied in this study. Forty-six samples were recruited using a non-probability sampling such as consecutive sampling and assigned to the intervention group (n=23) and the control group (n=23). The intervention group did the relaxation two times per day for two weeks, then no intervention for the control group. Significant findings were analyzed using chi-square. There was a statistically significant difference between groups regarding daily sleep time, Pittsburgh Sleep Quality Index (PSQI) score, and sleep quality after the intervention. The results (p<0,05) showed that the mean intervention group PSQI score decreased from indicating significant differences in the decline PSQI score between the intervention and the control group. It was found that combined autogenic, and Benson relaxation as one of the non-pharmacological interventions effectively improved participants' sleep quality. Instruct pregnant women about appropriate non-pharmacological interventions which have no side-effects to enhance the quality of sleep Results: there was a statistically significant difference between groups regarding daily sleep time, Pittsburgh Sleep Quality Index (PSQI) score and sleep quality after intervention. The results (p<0,05) showed that the mean intervention group PSQI score decrease from indicating that there were significant differences in the decrease PSQI score between the intervention and the control group. Conclusion: It was found that combined autogenic and benson relaxation as one of the non-pharmacological interventions was effective in improving participants sleep quality. Instruct pregnant women about appropriate non-pharmacological interventions which have no side-effects to improve sleep quality.